Young school children's use of digital devices and parental rules. Issue 4 (November 2015) - W. L. Goh, Wendy; Bay, Susanna; Chen, Vivian Hsueh-Hua
Highlights Children voluntarily souk parental approval to use digital device. Major parental rule on device use is to set time limits. Playing games is the most common activity.